A study of some characteristics of structure, meaning and culture of English idioms about animals - Phạm Thị Tố Như.; Nguyễn Văn Mười, Ph.D. (Hà Nội : Đại học Ngoại ngữ Hà Nội, 1998)
This thesis presents a study of some characteristics of structure, meaning and culture of English idioms about animals.
Keywords: Anh ngữ; English Idioms; English thesis; Luận văn Anh ngữ; Usage of English; English linguistics -- Usage